Measuring the Executorial Power of the Constitutional Court of the Republic Indonesia Decisions - Muwahid, Muwahid; Bagus, Moh. (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2023)
This study aims to measure the binding strength of the Constitutional Court's decision in constitutional review cases and to analyze the juridical implications of normalizing norms declared unconstitutional by the Constitutional Court. This research is normative legal research with a statutory approach, a concept approach, and a case approach. The Legislative Approach is used to make an inventory of laws and regulations relating to the position and authority of the Constitutional Court. The conceptual approach analyses legal issues based on concepts related to the executive power of the Constitutional Court's decision. The case approach is used as an object in this research, namely the findings of the Constitutional Court, which are not followed up. The results show that the Constitutional Court's decisions are normatively final and binding, but in reality, several Constitutional Court decisions are not followed up by the legislators; this gives the impression that the Constitutional Court's findings do not have an executive nature. The juridical implication of the normalization of norms is declared unconstitutional by the Constitutional Court. Juridically the model does not have binding legal force, and the cancellation of the legal standard must be carried out.